Aspek Hukum Penerapan Asas Kebebasan Berkontrak Terhadap Perjanjian Kredit Komsumtif Pada Bank Papua Kantor Cabang Kota Jayapura - Pelupessy, Berd Elkiopas; Pelupessy, Sella Petrix; Hamonangan, Sobardo (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine, analyze and clearly describe the application of the principle of freedom of contract in consumer credit agreements at Bank Papua, Jayapura City Branch Office and the form of legal protection that should be given to debtor customers as a form of implementation of the principle of freedom of contract that is responsible at Bank Papua, Jayapura City Branch Office. This research method is normative legal research or often also called doctrinal research. Normative legal research is carried out by examining library materials which are secondary data. The approach used in normative legal research is the statute approach and the conceptual approach. The results of the study revealed that the application of the principle of freedom of contract to credit agreements at Bank Papua, Jayapura City Branch Office, in credit agreements is categorized as a failure to implement policies that are non-implementation (cannot be implemented). This is evidenced by the many standard clauses that tend to protect creditors without paying attention to the rights of debtors. In practice, the standard clauses in the working capital credit agreement can be said to be biased, while the principle of balance also needs to be considered in making an agreement, but not enough through legal substance, but the bureaucratic apparatus and the community play an important role so that the law can work in society. Therefore, to reduce the risks faced in banking credit agreements, the active role of the government is very much needed by bank credit customers, namely by tightening supervision in terms of the use of standard agreements. This aims to ensure that bank credit customers as the weaker party can better protect their rights. As well as bank credit customers must be more active in fighting for their rights and more critical in examining the clauses in the credit agreement.